Occurrence of pharmaceuticals and cocaine in liver and muscle of different fish species from a Brazilian coastal zone - Roveri, Vinicius; Souza, Ursulla Pereira; da Costa, João Henrique Alliprandini [UNESP]; Toma, Walber; dos Anjos Caivano, Simone; Correia, Alberto Teodorico; Guimarães, Luciana Lopes (Elsevier, 2025)
The objective of the present study was to evaluate, for the first time, the occurrence of twelve pharmaceutically active compounds (PhACs) in the livers and muscles of five fish species in a Brazilian coastal zone. The species (Cathorops spixii, Genidens genidens, Bagre marinus, Larimus breviceps and Pellona harroweri) were selected based on their habitat, and presence in the human diet within the aforementioned coastal zone. The results demonstrated the presence of acetaminophen (ACE), benzoylecgonine (BEN), caffeine (CAF), cocaine (COC), and furosemide (FUR) in the fish tissues, with concentrations ranging from the limit of quantification (LOQ) to 9.17 ng g−1. A comparative analysis of the species revealed that C. spixii exhibited the highest accumulation of pharmaceutical agents in both muscle and liver tissues. In particular, the detection of ACE (a compound with low lipophilicity) was observed exclusively in the muscle of C. spixii. Despite its low lipophilicity, the concentrations of CAF were quantified in B. marinus at a level higher than those in C. spixii, G. genidens and L. breviceps. One potential explanation for this observed bioaccumulation of CAF in these species is the historical detection of high concentrations of this compound in this coastal zone. Furthermore, the observed discrepancy between the high levels of COC in relation to BEN in the tissues of C. spixii and L. breviceps can be attributed to the low lipophilicity of BEN and moderate hydrophobicity of COC. Ultimately, the observed contamination has the potential to result in secondary human exposure to PhACs.